Contribuição para o estudo da técnica cultural da cana de açúcar no estado de São Paulo - Arruda, Homero Corrêa de (1961)
Sugar cane which has been amongst the most important crops in the region of S. Paulo, Brazil, was however, until 1937, a type of culture based on routine and tradiction. This paper deals with a series of experiments which were planned to give technical bases to the most importart cultural proctices. Planting spaces, planting methods, varieties, harvesting times, methods of cultivation either of plant cane or stubble cane were studied and the following conclusions were drawn. Of the planting spaces studied (1,00, 1,20, = 1,4), 1,60 and 1,80 meters), the highest tonnage was obtained for the 1,00 and 1,20 meters spacings which, however, are not considered as practical on account of the difficulties for mecanical cultivation. The wider planting spaces (1,40 and 1,60) are considered as actually more advisable for all varieties studied: Co. 419, Co. 290 and G.P. 34-1200. Varietal competition in combination with harvesting times (3) experiments have shown that in a total of eight varieties the first two classified on the basis of tons. per Ha, were: Co. 419, C.B. 40-69, which, however, were the most sensitive to variations on harvesting times, and should therefore, be harvested in the three first months of the harveting season. Of the types of seed pieces compared, the one of the wholly cane, either with or without trash subdivided in the furrow has show to be the most practical and economical incomparison to the common type of the selected three buds seed pieces. Of the mechanical cultivation methods studied a combination of the Planet Jr. cultivator completed by hand hoeing gave higher yields than the others, but the most practical is a tractor cultivator followed by hand hoeing, for the first year crop. The experiment on stubble cane cultivation, comparing burning trash system with partial mulching, showed no differences in production, in a general way. If, however, complet mulching is left and further cultivation is not provided there occur a decrease in production, in relation to the methods which are supposed to be followed by mecanical cultivation. In one experiment comparing chemical cultivation by pre-emergence sprays with 2,4-D either as ether or amine, with the system or hand hoeing and mechanical cultivation. There was a difference in production favorably to the herbicidal system for the first 50-60 days following planting, which is interesting either from the economical or practical viewpoint. In an experiment planned to study several times of trash burning, followed by usual mechanical cultivation compared with several times of partial mulching after harvesting, it is concluded that trash burning did not affect production when practiced until 30 days after harvesting and the partial mulching had similar effect until the 45th day. In an experiment to study the possible effect of the detrashing operation of standing cane either in cane or sugar production as compared with common system adopted in S. Paulo, it is concluded that there is no reason for that practice which is adopted yet in Northeastern region of Brazil. Comparing several planting times of sugar cane under two different conditions, intercarlarlly to corn rows at 3 meters and the sugar cane rows at 1.50 meters and the common system of planting on naked soil it is concluded that February and early March are the best planting times for sugar cane and corn plant does not affect sugar cane production. As there occurred a production of 1.500 kilograms of corn grain per Ha, the method is considered as interesting either from the practical or the economical viewpoint.